2015
DOI: 10.1007/s11606-015-3231-8
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Strategies for Improving Control of Hypertension Among Patients with Usual Source of Care in the United States: The Blood Pressure Control Model

Abstract: BACKGROUND: Only half of hypertensive adults achieve blood pressure (BP) control in the United States, and it is unclear how BP control rates may be improved most effectively and efficiently at the population level. OBJECTIVE: We sought to compare the potential effects of system-wide isolated improvements in medication adherence, visit frequency, and higher physician prescription rate on achieving BP control at 52 weeks. DESIGN: We developed a Markov microsimulation model of patient-level, physician-level, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 52 publications
1
20
0
2
Order By: Relevance
“…The medication adherence rate found in this study was much lower than that reported in some developed countries such as the USA (51.3%), Germany (56.3%) and the UK (58.4%). 25 27 The adherence rate was also lower than that in other developing countries such as Palestine (45.7%), 28 Jordan and Lebanon (55.9%), 29 and the percentage of adherence is even lower than that in other developed regions in China, such as Shanghai, 19 as well as Hong Kong. 20 Cultural and economic factors are crucial factors which could explain different levels of adherence among different populations.…”
Section: Discussionmentioning
confidence: 71%
“…The medication adherence rate found in this study was much lower than that reported in some developed countries such as the USA (51.3%), Germany (56.3%) and the UK (58.4%). 25 27 The adherence rate was also lower than that in other developing countries such as Palestine (45.7%), 28 Jordan and Lebanon (55.9%), 29 and the percentage of adherence is even lower than that in other developed regions in China, such as Shanghai, 19 as well as Hong Kong. 20 Cultural and economic factors are crucial factors which could explain different levels of adherence among different populations.…”
Section: Discussionmentioning
confidence: 71%
“…Instead, we used antihypertensive medication use and visiting a doctor for a routine checkup in the past year as proxy assessment for hypertension management. Previous research has found that antihypertensive medication use and regular doctor visits were related to better BP control.…”
Section: Discussionmentioning
confidence: 94%
“…Further, Fontil, et al demonstrated in an individual-level Monte Carlo microsimulation model of BP management that idealized medication intensification had a far greater effect on improving BP control rates compared with UC (71% vs. 18%) than either increasing visit frequency (35%) or medication adherence (26%). 22 When all three processes were idealized, BP control was predicted to be 95%. Thus, although adherence to medication therapy is necessary, it may not be sufficient for achieving blood pressure control.…”
Section: Discussionmentioning
confidence: 99%